2017
DOI: 10.2334/josnusd.16-0624
|View full text |Cite
|
Sign up to set email alerts
|

Low-intensity pulsed ultrasound inhibits lipopolysaccharide-induced IL-6 and RANKL expression in osteoblasts

Abstract: Periodontal disease is caused by inflammation induced by Porphyromonas gingivalis (P.g.) lipopolysaccharide (LPS) and involves expression of proinflammatory cytokines such as interleukin (IL)-1, IL-6, tumor necrosis factor-α, and receptor activator of nuclear factor kappa B ligand (RANKL), which are implicated in bone resorption. Low-intensity pulsed ultrasound (LIPUS) is commonly used in the treatment of bone fracture. However, the mechanisms by which LIPUS inhibits LPS-induced inflammatory cytokines are poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…LIPUS is transmitted as an extracellular mechanical force at the cell membrane, where it is transduced into intra‐cellular electrical and/or biochemical signals. This stimulus can induce various cellular events, including mesenchymal stem cell recruitment, osteoblast proliferation, osteogenic differentiation, inflammation suppression, promotion of cytokine secretion, improvement of angiogenesis, extracellular matrix production and mineralization (Angle, Sena, Sumner, & Virdi, ; Doan, Reher, Meghji, & Harris, ; Hu et al, ; Huang et al, ; Nagao et al, ; Takayama et al, ; Uddin & Qin, ; Yang, Ren, Deng, Wang, & Song, ; Young & Dyson, ). Furthermore, some studies have reported that LIPUS promotes cementoblast differentiation (Inubushi et al, ) and the migration (Wang, Li, et al, ) and pluripotent characteristics (El‐Bialy, Alhadlaq, & Lam, ) of periodontal ligament cells.…”
Section: Introductionmentioning
confidence: 99%
“…LIPUS is transmitted as an extracellular mechanical force at the cell membrane, where it is transduced into intra‐cellular electrical and/or biochemical signals. This stimulus can induce various cellular events, including mesenchymal stem cell recruitment, osteoblast proliferation, osteogenic differentiation, inflammation suppression, promotion of cytokine secretion, improvement of angiogenesis, extracellular matrix production and mineralization (Angle, Sena, Sumner, & Virdi, ; Doan, Reher, Meghji, & Harris, ; Hu et al, ; Huang et al, ; Nagao et al, ; Takayama et al, ; Uddin & Qin, ; Yang, Ren, Deng, Wang, & Song, ; Young & Dyson, ). Furthermore, some studies have reported that LIPUS promotes cementoblast differentiation (Inubushi et al, ) and the migration (Wang, Li, et al, ) and pluripotent characteristics (El‐Bialy, Alhadlaq, & Lam, ) of periodontal ligament cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 During past decades, emerging evidences revealed that LIPUS treatment could reduce the expression of pro-inflammtory cytokines, limit the infiltration of inflammatory cells and modulate the phenotype of inflammatory cells in a series of bone and joint diseases, and consequently accelerate the recovery from diseases. [8][9][10][11] Moreover, recent animal experiments demonstrated that LIPUS could also benefit several cardiovascular diseases, such as left ventricular remodelling induced by chronic myocardial ischaemia and transverse aortic constriction (TAC), where mechanical stimulation of caveolin-1 and regulation of its downstream intracellular signallings were critically involved. [12][13][14] However, so far the effect of LIPUS on acute viral myocarditis was never investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Having dual roles, IL‐6 acts as either pro‐ or anti‐inflammatory signaling agents 66,67 . At the initial phase of periodontitis, the gram‐negative pathogens and their lipopolysaccharides activates transcription of proinflammatory cytokines in affected host cells via the NFκB pathway, 68‐70 resulting in IL‐1, IL‐6, and TNF‐α production and related matrix metalloproteinase activation leading to degradation of periodontal extracellular matrix and bone resorption through increased RANKL secretion 71,72 . IL‐6 activates transcription mediated by nuclear factor of activated T cells leading to production of IL‐4 by naïve CD4+ T cells and their differentiation into effector Th2 cells 18 .…”
Section: Discussionmentioning
confidence: 99%